Morphological and molecular profiling of an entomopathogenic nematode Steinernema feltiae: Unlocking its biocontrol potential against vegetable insect pests - Janardhan, Hiriyannanahalli Narayanaswamy; Askary, Tarique Hassan; Bhat, Aashaq Hussain; Rana, Aasha; Ahad, Ishtiyaq; Al-Qahtani, Wahidah H. (Zootaxa, 2023)
A population of entomopathogenic nematodes, belonging to the Feltiae-clade and labelled J13, was discovered in the agricultural soils of the hilly regions of the Union territory of Jammu and Kashmir, India. Based on morphological, morphometric, and molecular analyses, the nematodes were identified as Steinernema feltiae. The J13 nematode isolate was tested in a laboratory assay for its pathogenicity against six major pests of vegetable crops: Pieris brassicae, Plutella xylostella, Helicoverpa armigera, Agrotis iplison, Trichoplusia ni, and Exelastis atomosa. The morphology of the isolated nematode closely matched the original description, except for the adult females, which had prominent epiptygmata instead of the weakly developed, double-flapped epiptygmata described in the original report. Analysis of the internal transcribed spacer and large subunit rRNA data from the J13 nematodes showed 100% similarity to sequences of the type population, indicating that they are conspecific. The virulence assays revealed that the nematode caused 100% mortality in the tested insect pests within 48–72 hours, even at the lowest concentration of 50 infective juveniles per insect. The calculated median lethal concentration varied among the pests, with the lowest number of infective juveniles needed to achieve 50% larval killing being 117 for P. xylostella, 181.74 for P. brassicae, 226.35 for H. armigera, and 202.07 for T. ni at 24 hours post-inoculation. These findings suggest that S. feltiae isolated during the present investigation, may be a viable option for the biocontrol of these insect pests in Kashmir valley, India.